What tactical and technical comments do coaches make during netball matches? A content analysis in netball. (2nd January 2021) - Croft, Hayden; Spencer, Kirsten; Robertson, Sam
ABSTRACT: In sport, an "explosion" of information has meant that coaches may not have the time or cognitive resources to integrate it effectively into their decision-making. Research suggests that a disconnect exists between the information provided from the "sport scientist to coach", and subsequently between "coach to player". Further investigation is required to determine the detail within the tactical and technical instruction, with the aim of creating better alignment and implementation between the performance data collected and actual coach requirements during a game. Using inductive content analysis, with an independent researcher acting as a "critical friend", themes and dimensions were extracted from audio recordings of six coaches' (ANZ Premiership netball) conversations during competition. Analysis of the transcribed recordings found that the coaches discussed the technical and tactical elements of the game 695 times, within five general dimensions; movement (38.4%), actions (23.9%), positioning (17.3%), possession outcomes (10.6%) and strategy (9.8%). Within these 5 dimensions there were 17 higher order themes including; and 56 lower order themes. This study shows five dimensions that a performance analyst can use when designing data collection workflows. These themes are discussed in relation to the latest performance analysis literature and highlight the need for further research into the data sources that can provide information about them.